Literacy Training to Increase Students Reading Interest in Gending II State Elementary School - Ryzca Siti Qomariyah; Ani Anjarwati; Ika Silviana; Tria Riasih; Fathimatus Zahra (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2021)
The School Literacy Movement has an important role in increasing students' interest in reading, so we took the initiative to serve the school so that it can increase student interest in reading which is starting to decline. The method we use is a service method where the main target for mentoring is fourth grade students at Gending II State Elementary School. The activity was carried out for one week, from 09 May 2022 to 20 May 2022. We re-managed the monotonous reading corner so that students are interested in reading and add reading books for students. The expected result is that students can reuse the reading corner and the school can facilitate it according to student needs.